2005
DOI: 10.1152/jn.00255.2005
|View full text |Cite
|
Sign up to set email alerts
|

Synaptically Released GABA Activates Both Pre- and Postsynaptic GABAB Receptors in the Rat Globus Pallidus

Abstract: Kaneda, Katsuyuki and Hitoshi Kita. Synaptically released GABA activates both pre-and postsynaptic GABA B receptors in the rat globus pallidus. J Neurophysiol 94: 1104 -1114, 2005; doi:10.1152/jn.00255.2005. The globus pallidus (GP) contains abundant GABAergic synapses and GABA B receptors. To investigate whether synaptically released GABA can activate pre-and postsynaptic GABA B receptors in the GP, physiological recordings were performed using rat brain slice preparations. Cell-attached recordings from GABA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
59
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 57 publications
(73 reference statements)
11
59
0
Order By: Relevance
“…The effects of the GABA B receptor antagonist CGP55845 were similar to those caused by increasing extracellular Ca 2ϩ , consistent with the observation that CGP55845 preferentially inhibits presynaptic GABA B receptors (Yamada et al 1999; see also Chen and Yung 2005;Fearon et al 2003;Jensen et al 1999;Kaneda and Kita 2005;Than and Szabo 2002). Moreover, the action of CGP55845, by occurring in the first response in a train, reveals the blockage of GABA B receptors that were tonically activated.…”
Section: Regulation Of Release Probability By Tonic Gaba B Receptor Asupporting
confidence: 82%
See 2 more Smart Citations
“…The effects of the GABA B receptor antagonist CGP55845 were similar to those caused by increasing extracellular Ca 2ϩ , consistent with the observation that CGP55845 preferentially inhibits presynaptic GABA B receptors (Yamada et al 1999; see also Chen and Yung 2005;Fearon et al 2003;Jensen et al 1999;Kaneda and Kita 2005;Than and Szabo 2002). Moreover, the action of CGP55845, by occurring in the first response in a train, reveals the blockage of GABA B receptors that were tonically activated.…”
Section: Regulation Of Release Probability By Tonic Gaba B Receptor Asupporting
confidence: 82%
“…The inset shows exponential fitting to the decay of an IPSC in the train, which was needed to determine the baseline from which the amplitude of the subsequent IPSC could be measured. B: plot of normalized eIPSC peak amplitude (mean Ϯ MSE) in the train for 8 experiments, like those shown in A (0.5 mM [Ca 2ϩ ] o , n ϭ 5; 2 mM [Ca 2ϩ ] o , n ϭ 8 high-affinity GABA B receptor blocker CGP55845, which is reported to act preferentially on presynaptic GABA B receptors (Chen and Yung 2005;Fearon et al 2003;Jensen et al 1999;Kaneda and Kita 2005;Than and Szabo 2002;Yamada et al 1999). Another GABA B receptor antagonist, CGP35348 (Deisz et al 1997;Morishita and Sastry 1995;Mouginot et al 1998), was not used since it is known to block postsynaptic GABA B receptors at the Golgi cell-granule cell synapses and could generate spurious effects on eIPSCs .…”
Section: Modulation Of Inhibitory Neurotransmission By Gaba B Receptorsmentioning
confidence: 95%
See 1 more Smart Citation
“…This is in accordance with previous findings that GABA B Rs are localized in perisynaptic (Kulik et al, 2002) and extrasynaptic (Kulik et al, 2003) sites, although it remains unclear whether this is also true of the SC, and that affinity of GABA for GABA B Rs is lower than that for GABA A Rs (Curtis et al, 1970;Chu et al, 1990). We also found that repetitive stimulation was required to activate GABA B Rs in the SC, as has been observed in various brain regions (Johnson et al, 1992;Isaacson et al, 1993;Mitchell and Silver, 2000;Saitoh et al, 2004;Kaneda and Kita, 2005).…”
Section: Synaptically Released Gaba Activates Gaba B Rs In the Scsupporting
confidence: 76%
“…The bath contained CNQX and APV. The stimulating electrodes were placed just ventral to the SC, and repetitive stimulation (20 -50 pulses at 50 Hz) was delivered to elicit the large amount of GABA release that should be necessary for activating GABA B receptors (Isaacson et al, 1993;Mitchell and Silver, 2000;Kaneda and Kita, 2005;Kaneda et al, 2008). Although this stimulation would activate both nigral and other passing GABAergic fibers, including those from the zona incerta and reticular formation (Ficalora and Mize, 1989;Appell and Behan, 1990;Kim et al, 1992;May et al, 1997;Kolmac et al, 1998), the stimulation-evoked IPSCs were not affected by bath application of the selective GABA B receptor antagonist CGP52432 (3 M) in six of six neurons tested (Fig.…”
Section: Electrophysiological Properties Of Snr Inhibition To Sgi Gabmentioning
confidence: 99%